Pengembangan Aspek Psikomotorik Siswa Sekolah Menengah Atas Negeri 2 Ulunoyo dalam Mengajar Sekolah Minggu - Arozatulo Telaumbanua (Sekolah Tinggi Teologi Real Batam, 2022)
Teaching Sunday School needs effective, creative, innovative and dynamic psychomotor to produce a good and quality teaching process. A Sunday School teacher should not underestimate Sunday School children in understanding God's Word. Some Sunday School teachers think children are not critical, the fact they have complex skills. The majority of Sunday School teachers are educated or currently sitting in high school. Thus, the psychomotor aspect really needs to be developed through trainings carried in schools and churches. Because teaching Sunday school cannot be carried like a sermon at Sunday worship in church, but Sunday school activities are full of creations and are colored with a joyful and fun atmosphere for children. The purpose is to improve the skills of State High School 2 Ulunoyo students in teaching creative Sunday schools. A combination of lecture, question and answer and role-playing methods was used. As a result of this community service, students better understand the importance of creation in Sunday school teaching, add experience and give new enthusiasm to be involved in Sunday school activities in their respective churches. They are very enthusiastic about participating in this activity and implementing it in the Sunday school ministry where they serve.Keywords: evelopment; psychomotor; students; teaching; sunday school AbstrakMengajar Sekolah Minggu perlu psikomotorik yang efektif, kreatif, inovatif dan dinamis untuk menghasilkan proses pengajaran yang baik dan berkualitas. Dalam mengajar Sekolah Minggu, seorang guru Sekolah Minggu tidak boleh menganggap remeh anak Sekolah Minggu dalam memahami Firman Tuhan. Sebagian guru Sekolah Minggu beranggapan bahwa anak sekolah minggu tidak kritis. Namun yang benar faktanya ialah anak Sekolah Minggu memiliki keterampilan yang kompleks. Guru Sekolah Minggu mayoritas berpendidikan atau sedang duduk dibangku Sekolah Menengah Atas. Dengan demikian aspek psikomotorik sangat perlu dikembangkan melalui pelatihan-pelatihan yang dilaksanakan di sekolah maupun di gereja. Sebab mengajar sekolah minggu tidak dapat dilaksanakan seperti khotbah pada ibadah minggu atau ibadah raya di gereja, tetapi kegiatan sekolah minggu penuh dengan kreasi-kreasi dan diwarnai dengan suasana yang sukacita serta menyenangkan bagi anak sekolah minggu. Tujuan kegiatan pengabdian kepada masyarakat ini adalah untuk meningkatkan keterampilan siswa Sekolah Menengah Atas Negeri 2 Ulunoyo dalam mengajar sekolah minggu yang kreatif. Dalam kegiatan tersebut, digunakan metode kombinasi antara ceramah, tanya jawab dan bermain peran. Hasil dari pengabdian kepada masyarakat ini, siswa lebih memahami pentingnya kreasi dalam mengajar sekolah minggu, menambah pengalaman dan memberikan semangat baru untuk terlibat dalam kegiatan sekolah minggu di gereja masing-masing. Mereka sangat antusias mengikuti kegiatan ini dan menerapkan di pelayanan sekolah minggu di mana mereka melayani.Kata Kunci: pengembangan; psikomotorik; siswa; mengajar; sekolah minggu